2002
DOI: 10.1002/ijc.10843
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of galectins‐1 and ‐3 in human colon cancer and their role in regulating cell migration

Abstract: To probe the potential contribution of ␤-galactoside-contributing epitopes and receptor proteins (gal-1 and gal-3) to colon malignancy, we first examined the expression of galectins and binding sites in clinical specimens by lectin and immunohistochemistry. Sixty-seven colonic surgical resections were studied, including 10 normal, 10 mild dysplasias, 10 severe dysplasias and 37 cancers. gal-1 and gal-3 were expressed in variable amounts in the epithelial cells and the connective tissue of normal colon. Their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 48 publications
6
100
0
3
Order By: Relevance
“…recent evidence suggests that the interaction between tumor cells and surrounding stroma plays a critical role in tumor growth, invasion, metastasis, angiogenesis, and chemoresistance (29)(30)(31)(32)(33)(34). It has been shown that galectin-1 regulates cell migration and that galectin-1 binding sites are displayed on cell surfaces in most colon cancer cell lines, while only one of them actually expresses galectin-1 (16). taken together, galectin-1 expression by stroma may play a role in colon cancer cell migration via a paracrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…recent evidence suggests that the interaction between tumor cells and surrounding stroma plays a critical role in tumor growth, invasion, metastasis, angiogenesis, and chemoresistance (29)(30)(31)(32)(33)(34). It has been shown that galectin-1 regulates cell migration and that galectin-1 binding sites are displayed on cell surfaces in most colon cancer cell lines, while only one of them actually expresses galectin-1 (16). taken together, galectin-1 expression by stroma may play a role in colon cancer cell migration via a paracrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…18 The specificity of the galectin-3 antibody was checked by immunoblotting and ELISA assays with controls to exclude any crossreactivity to other galectins (especially galectin-1, which is abundant in human lungs), as previously detailed. [18][19][20]33 An internal positive control consisted in the expression of galectin-3 (also labeled Mac-2) by alveolar macrophages. The negative control sections were immunostained under the same conditions, but with the omission of the primary antibody.…”
Section: Galectin-3 Expression In Lung Carcinomasmentioning
confidence: 99%
“…15,16 Galectins are involved in cell growth, apoptosis and cell migration features. [17][18][19][20] Of these 14 galectins, galectin-3, a chimera-type galectin, is of special interest since its structure harbors a sugar-combining site, a collagensensitive stalk and a short N-terminated section, acting as a target for phosphorylation. 21 What is particularly intriguing about this sole chimera-type galectin is its presence in nuclear, cytoplasmic and extracellular sites, 22 its ability to interact with a variety of carbohydrate and protein ligands and to form pentamers with unique crosslinking abilities, 23 its strong antiapoptotic activity coupled with the nuclear export of the phosphorylated form (for example in chemotherapeutic treatment), 24 and its effect on promoter activity of cyclin D1, 25 which is a prognostic marker in the adenocarcinoma subgroup of lung carcinomas.…”
mentioning
confidence: 99%
“…59 Furthermore, galectin-3 itself can bind LNs, 60 and multimeric galectin-3 complexes are known to influence cell adhesion and migration. Thus, galectin-3 has been shown to reduce migration of colon carcinoma cells 61 and to support migration of breast cancer cells. 62 Previously, galectin-3 was shown to interact with a3b1 and NG2 proteoglycan, with an impact on cell motility.…”
Section: C44a Associates With Galectin-3mentioning
confidence: 99%